Halal tourism / Yong Azrina Ali Akbar - Ali Akbar, Yong Azrina (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Halal tourism is “any tourism object or action which is permissible according to Islamic teachings to be used or engaged by Muslims in the tourism industry” (Battour & Ismail, 2016). According to Mohsin, Noriah Ramli and Alkhulayfi, (2016), halal tourism refers to the provision of tourism products and services that meet the needs of Muslim travellers to facilitate their worship and dietary requirements that conform to Islamic teachings. Recently, Muslim travel market continues to grow and evolve. As reported by Global Muslim Travel Index (2019), there are nine factors influencing the consumption behaviour of Muslim travellers which are halal food, prayer facilities, water-friendly washrooms, absence of Islamophobia, social reasons, Ramadhan services, and local Muslim experiences, recreational spaces with privacy and no non-halal services.